2019
DOI: 10.1155/2019/4983291
|View full text |Cite
|
Sign up to set email alerts
|

Nanoenabled Bioseparations: Current Developments and Future Prospects

Abstract: The use of nanomaterials in bioseparations has been recently introduced to overcome the drawbacks of the conventional methods. Different forms of nanomaterials, particularly magnetic nanoparticles (MNPs), carbon nanotubes (CNTs), casted nanoporous membranes, and electrospun nanofiber membranes were utilized in biological separation for the aim of production of different biomolecules such as proteins, amino acids, nucleic acids, and enzymes. This paper critically reviews the state-of-the-art efforts undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…Another recent study reported PDT combined with curcumin-loaded magnetic/photoresponsive liposomes (MPLs) in treating papillomavirus-related cancers ( Figure 5 ) [ 87 ]. Citric acid-coated iron oxide (CMNPs) magnetic nanoparticles are synthesized employing the chemical precipitation method [ 88 ]. Liposomes were prepared using thin-film hydration technique and lipid mixtures in a molar ratio of 5 DSPC: 3 Chol: 1 DDAB (1,2-stearoyl-sn-glycero-3-phosphocholine, dimethyl octadecyl ammonium bromide).…”
Section: Liposomal Photosensitizer Formulations For Tumor Photodynamic Therapymentioning
confidence: 99%
“…Another recent study reported PDT combined with curcumin-loaded magnetic/photoresponsive liposomes (MPLs) in treating papillomavirus-related cancers ( Figure 5 ) [ 87 ]. Citric acid-coated iron oxide (CMNPs) magnetic nanoparticles are synthesized employing the chemical precipitation method [ 88 ]. Liposomes were prepared using thin-film hydration technique and lipid mixtures in a molar ratio of 5 DSPC: 3 Chol: 1 DDAB (1,2-stearoyl-sn-glycero-3-phosphocholine, dimethyl octadecyl ammonium bromide).…”
Section: Liposomal Photosensitizer Formulations For Tumor Photodynamic Therapymentioning
confidence: 99%
“…Consequently, several delivery systems, including liposomes, macrocycles, and polymeric nanoparticles, were reported to significantly enhance the therapeutic effects of various natural and synthetic drugs [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Some natural and synthetic polymers were found to have healing properties by improving proliferation and increasing the cell count.…”
Section: Introductionmentioning
confidence: 99%
“…It is a simple, cost-effective, and efficient approach in contrast to conventional methods [17] . MNPs offer various advantages like lower aggregation, enormous surface area, easy modulation under EMF, one-pot separation, and flexible particle size [109] , [110] , [111] . Moreover, the efficiency of magnetic bioseparation can be enhanced by surface functionalization of MNPs with various biocompatible polymers, organic and inorganic biomolecules [109] .…”
Section: Biomedical Application Of Hp-mnpsmentioning
confidence: 99%